Dose-intensified bendamustine followed by autologous peripheral blood stem cell support in relapsed and refractory multiple myeloma with impaired bone marrow function - Breitkreutz, Iris; Kosely, Florentina; Heining, Christoph; Hillengaß, Jens; Egerer, Gerlinde; Ho, Anthony Dick; Goldschmidt, Hartmut; Raab, Marc-Steffen (Hematological oncology, 2016)
Therapeutic options in heavily pretreated relapsed/refractory multiple myeloma patients are often very limited because of impaired bone marrow function. Bendamustine is effective in multiple myeloma and has a favourable toxicity profile. We hypothesized that dose-intensified bendamustine (180 mg/m2, day 1 and 2) followed by autologous blood stem cell support (ASCS) would improve bone marrow function with low post-transplant toxicity in patients with severely impaired haematopoiesis. We analyzed 28 consecutive myeloma patients, with a median of three prior lines of therapy (range 2-7), who had relapsed from the last treatment with very limited bone marrow function and were therefore ineligible for conventional chemotherapy, novel agents or trial enrolment. Dose-intensified bendamustine with ASCS improved haematopoiesis as reflected by increased platelet counts (median 40/nl vs 94/nl, p = 0.0004) and white blood cell counts (3.0/nl vs 4.8/nl, p = 0.02) at day +100. The median time until engraftment of platelets (>50/nl) was 11 days (0-24 days) and of white cell counts (>1.0/nl) 0 days (0-24 days). At least, a minimal response was achieved in 36% of patients. The disease stabilization rate was 50% while the median progression-free survival rate was limited to 2.14 months. Most importantly, patients were once again eligible for alternative treatments including enrolment into clinical trials. We conclude that dose-intensified bendamustine followed by ASCS is safe and feasible for multiple myeloma patients with very limited bone marrow reserve. Copyright © 2015 John Wiley & Sons, Ltd.